Assessing the effectiveness of the fight against public-sector corruption in Mauritius: Perception v reality. (December 2020) - Peerthum, Sheilendra; Gunputh, Rajendra Parsad; Luckho, Takesh
Abstract: Purpose : The purpose of this research is to examine and analyse public corruption by comparing citizens' assessment of the perceived performance of the anti-corruption agency of Mauritius (ICAC), in terms of its prosecutorial efficacy, and comparing such perception with the reality reflected by court judgments. Design/Methodology/Approach : A survey was carried out using a structured questionnaire, to gauge public opinion on the perceived effectiveness of the ICAC in fighting public corruption. Specific results were then cross-validated against an analysis of court judgments. Findings : The survey findings reveal that citizens have a negative opinion on ICAC's effectiveness and this perception is justified and validated by a content analysis exercise, to confirm poor prosecutorial performance. Originality/Value : The study seeks to sensitise decision-makers on the need to instil public trust by clarifying specific provisions of the anticorruption legislation and adopting a proactive approach by setting up an integrity system within public organisations to address public corruption.